REGISTER IN FIT AND HEALTHY LIFESTYLE FORUM ON KASKUS - HERNAWAN, OKTAVIAN ANGGA (Jurnal Ilmiah Mahasiswa FIB, 2014)
Keywords: Register, Field, Mode, Tenor, Fit and Healthy Life Style Forum Nowadays, people build or create communities based on the same interest, religion, region and many others. It shows that people in social community need a certain language to interact with the others in same social community. This leads to the fact that language is divided into some varieties. One of the varieties of language that isused in a community is register. This study was conducted to answer the researchquestions namely 1) what are the register used by the members of Fit and HealthyLifestyle, and 2) to what extent are aspects of situational context in register whichconsists of field, mode and tenor in FHL forum in Kaskus. This study uses descriptive qualitative method because the objects of this research deal with the exploration of human problem based on language phenomenon. In this study, the data were collected from members of internet forum on Kaskus. Thereare two kinds of data used in this study. First, the data are terms used in the interaction in FHL forum on Kaskus which is considered as register. The second data are in the form of register phenomenon of the interaction used by the participant in FHL forum. This study describes the registers phenomenon with the common meaning and particular meaning based on Dictionary and deep interview from the expert.There are 17 registers used by the members of Fit and Healthy Forum on Kaskus. Register itself have different meaning for the member. Some registers have literal meaning and register meaning and some do not. Based on the analysis, situationalcontext which contain of field, mode and tenor was important for the background of the object analysis. Situational context is influencing the use of word literally andspecifically when registers are used by the certain groups or society. Based on field,mode and tenor the writer can make a conclusion that registers are important for themember to reach their purpose or the point of communication.  The writer suggests the next researcher to do the analysis of registers based on written text as one of the ways to get the data source. However, the next researcher has to be in touch to get communication with the text writer of the data to get the best data. The next researcher can also analyze registers in community or group which use variation of language in communication.